Study of ways of modernization of the current-conducting part of overhead power lines - Cherkashyna, V. V.; Omelianenko, H. V.; Shmatov, Anton Oleksiyovych (Artmedia24, 2024)
A study of ways to modernize the current-conducting part of overhead lines was conducted in order to increase the efficiency of electric energy transmission. A comparative analysis of technical and economic characteristics of АS, ACCR, AERO-Z wires was performed. According to the results of the comparison of AS, ACCR, AERO-Z wires, it follows that the factor that limits the scope of application of ACCR wire in Ukrainian electrical networks, even for spans with extremely high requirements for the characteristics of electrical energy transmission, is its high cost. Also, during the research, it was found that the AERO-Z wire is the most appropriate for introduction into Ukrainian electrical networks. Because the technical characteristics of this wire are better than the character-istics of AS wire and it has a relatively low cost compared to ACCR wire, and its special design is adapted to adverse climatic conditions that affect the characteristics of electrical energy transmission.
Keywords: overhead power line; current-carrying part; wire; electrical network; criterial method